Comparison of Ferumoxytol-enhanced MR Angiography and CT Angiography for the Detection of Pulmonary Arteriovenous Malformations in Hereditary Hemorrhagic Telangiectasia: Initial Results - Khan, Sarah N. (Radiol Cardiothorac Imaging, 2020)
PURPOSE: To perform a preliminary comparison of the sensitivity and positive predictive value of ferumoxytol-enhanced MR angiography with those of CT angiography for detection of pulmonary arteriovenous malformations (AVMs) in hereditary hemorrhagic telangiectasia (HHT). MATERIALS AND METHODS: Institutional review board approval and informed patient consent were obtained. Ten patients with pulmonary AVMs who had undergone CT of the chest within 12 months underwent MRI of the chest and abdomen with ferumoxytol at 3.0 T at a dose of 4 mg per kilogram of body weight. Consensus review of MR and CT images assessed the presence and characteristics of pulmonary AVMs, image quality, vessel visibility, and artifact grade. RESULTS: Forty-three AVMs were detected, 13 native and 30 recanalized. Twenty-one AVMs had a feeding artery diameter of greater than 2 mm, of which detection occurred in 19 (at MRI and CT), in two (at MRI only), and zero (at CT only). Twenty-two AVMs had a feeding artery diameter of less than or equal to 2 mm, of which detection occurred in 16 (at MRI and CT), six (at CT only), and zero (at MRI only). For the entire cohort, the sensitivity of ferumoxytol-enhanced MRI using CT as the reference standard was 85.4% (35 of 41), and the positive predictive value was 100% (35 of 35). No significant difference was found between CT and MRI in AVM size, feeding artery and draining vein diameter, and artifact score (P >.05 for all). CONCLUSION: Initial results suggest that ferumoxytol-enhanced MRI is a feasible alternative to CT for detection of pulmonary AVM in HHT, while avoiding repeated exposure to radiation, nephrotoxic contrast material, or gadolinium-based contrast agent. © RSNA, 2020